Time Conciousness and Temporal Experiences: A Study on the Explanatory Limits of the Edmund Husserl’s Lectures on the Phenomenology of Inner Time Consciousness - Kretschel, Verónica (2014)
Husserlian phenomenology of time, as it is developed on theLectures on the Phenomenology of Inner Time Consciousness, shows some  difficulties  to  explain  certain  temporal  experiences.  This  is  the  case  of the incompatibility between the rigidity of the retentional modification and the effective approach that a subject may have with his memories. On the one hand, according to the Lectures’ explanation, the darkening of the past occurs in an homogeneous way: The more distant an experience is, the lower the clarity of the associated retention. However, our relation with the past is not so direct. Complementing the studies of the Lectureswith those of the Analysis concerning passive synthesiscould allow to explain this kind of temporal phenomena.